2018
DOI: 10.1186/s12872-018-0816-2
|View full text |Cite
|
Sign up to set email alerts
|

SHP2 inhibitor PHPS1 protects against atherosclerosis by inhibiting smooth muscle cell proliferation

Abstract: BackgroundSmooth muscle cells play an important role in the development of atherosclerosis. SHP2 is known to regulate the proliferation and migration of smooth muscle cells. The purpose of this study was to determine whether the SHP2 inhibitor PHPS1 has a pro-atherosclerotic or an atheroprotective effect in vivo and in vitro.MethodsAfter exposure to a high-cholesterol diet for 4 weeks, LDL receptor-deficient (Ldlr−/−) mice were exposed to the SHP2 inhibitor PHPS1 or vehicle. Body weight, serum glucose and lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
3
13
1
Order By: Relevance
“…In line with this, a recent study also showed that PTP1B deletion in ApoE −/− /LysM-PTP1B mice could reduce the size of atherosclerotic plaque [67]. Likewise, SHP2 has been identified as a drug target for acute myeloid leukemia [68,69] solid tumors [70], and atherosclerosis by negatively regulating smooth muscle cell proliferation [71]. We thereby hypothesize that nanotopography may synergize with the pharmacological inhibition of a specific target to promote desirable EC behaviors amenable to endothelialization.…”
Section: Discussionsupporting
confidence: 56%
“…In line with this, a recent study also showed that PTP1B deletion in ApoE −/− /LysM-PTP1B mice could reduce the size of atherosclerotic plaque [67]. Likewise, SHP2 has been identified as a drug target for acute myeloid leukemia [68,69] solid tumors [70], and atherosclerosis by negatively regulating smooth muscle cell proliferation [71]. We thereby hypothesize that nanotopography may synergize with the pharmacological inhibition of a specific target to promote desirable EC behaviors amenable to endothelialization.…”
Section: Discussionsupporting
confidence: 56%
“…We recently reported that SHP1, but not SHP2, reduces PD-L1-dependent regulation of T regulatory lymphocyte (Treg) function and is associated with resolution of shock- and sepsis-induced lung injury (Tang et al 2015 ). Additionally, previous research has demonstrated that SHP2 deficiency may have a protective effect in experimental renal (Hsu et al 2017 ; Teng et al 2018 ; Verma et al 2016 ) and cardiovascular (Chen et al 2018 ) injury. Thus, it appears that SHP2 activation may have differential effects depending on the location of action.…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that SHP1, but not SHP2, negatively modulated PD-L1 dependent regulation of T regulatory lymphocyte (Treg) function and in so doing contributed to resolving shock/sepsis-induced lung injury (Tang et al 2015). At the same time, some studies have revealed that SHP2 de ciency may have a protective effect in experimental renal (Hsu et al 2017, Teng et al 2018, Verma et al 2016) and cardiovascular (Chen et al 2018) conditions. Thus, SHP2 activation may play distinct roles in different organs.…”
Section: Introductionmentioning
confidence: 99%